Seroprevalence of syphilis and human immunodeficiency virus infections among pregnant women who attend the University of Gondar teaching hospital, Northwest Ethiopia: a cross sectional study - Endris, Mengistu (BMC Infect Dis, 2015)
BACKGROUND: Syphilis and HIV infections in pregnancy result in a number of adverse outcomes including neonatal death and vertical transmission. Ethiopia is a country where these infections are highly prevalent. However, data on co-morbidities of syphilis and HIV among pregnant women in Gondar are scarce. Thus, the aim of this study was to determine the seroprevalence of these infections and associated factors among pregnant women attending antenatal care at the University of Gondar teaching hospital, Northwest Ethiopia. METHODS: A cross sectional study was conducted from February to June 2011. Structured interviews were used to collect socio-demographic and obstetric data. Sera against syphilis were screened by rapid plasma reagin test; and confirmed by Treponema pallidum hemagglutination assay. HIV infection was detected by rapid HIV test kits following the national algorithms for HIV testing. Data were summarized by descriptive statistics and binary logistic regression. Odds ratio (OR) and 95% confidence intervals (CI) were calculated. RESULTS: Of 385 pregnant women, reactive syphilis was noted in 11/385 (2.9%) and seroprevalence of HIV was 43/385 (11.2%). The prevalence of syphilis and HIV co-infection was 2/385(0.5%). High rate of syphilis was observed among the women with above 30 years of age (OR 3.69, 95% CI 0.83 - 16.82). Women with a history of miscarriage and stillbirth were more likely to be infected by syphilis (OR 2.22, 95% CI 0.54-9.60) and (OR 3.24, 95% CI 0.00-17.54), respectively. CONCLUSION: Our data indicated that syphilis and HIV infections are still important public health concerns among pregnant women in the Gondar area. Hence, we recommend strenuous screening of all pregnant women for these infections during antenatal care. Further, strengthening health education on the mode of transmission and prevention of HIV and syphilis is essential for effective control of these infections.